IMPLEMENTASI PERMAINAN SUDOKU DALAM MENINGKATKAN PERTUMBUHAN KOGNITIF SISWA DALAM LINGKUNGAN BELAJAR - Sembiring, Thresia Yohana; Silangit, Menna Sri Ulina; Purba, Ricky Rikardo; Manik, Efron (Universitas Quality, 2024)
This research aims to provide a new innovation in mathematics learning, because based on the results interviews, researchers found that mathematics learning is less innovative, learning strategies are still monotonous and learning methods are less interesting so that students' cognitive growth is not optimal. The Sudoku game is a logic-based puzzle game that can improve junior high school students' cognitive abilities in a mathematics learning environment. Sudoku trains the student's mind to absorb several strategies and pieces of information in a short time. Apart from that, this game can also help improve students' memory and concentration. Sudoku can be used as a game choice that can increase students' concentration in learning mathematics.